2022
DOI: 10.1098/rsta.2021.0220
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing and predicting the relationship between translaminar fracture toughness and pull-out length distributions under distinct temperatures

Abstract: The translaminar fracture toughness reflects the damage tolerance of a fibre-reinforced composite under longitudinal tension, which often governs the final failure of structures. One of the main energy-dissipation mechanisms that contributes to the translaminar toughness of composites is the fibre pull-out process. The present study aims to quantify and model the statistical distribution of fibre pull-out lengths formed on the translaminar fracture surface of composites, for the first time in the literature; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Energy spent in debonding, fiber breakage, Fibrillation of fiber, and crack growth in the matrix due to stress concentration at the crack tip contributes to fracture toughness. 23,24 Previous studies show a higher decrease in fracture toughness of composites with reinforcement of alkali-treated natural fibers compared to untreated, caused by restriction to debonding and pull out of fibers that do not allow energy dissipation. 25 While various studies showed contrary responses of fracture toughness with increased fiber content, it may depend on the extent of fiber adhesion with matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy spent in debonding, fiber breakage, Fibrillation of fiber, and crack growth in the matrix due to stress concentration at the crack tip contributes to fracture toughness. 23,24 Previous studies show a higher decrease in fracture toughness of composites with reinforcement of alkali-treated natural fibers compared to untreated, caused by restriction to debonding and pull out of fibers that do not allow energy dissipation. 25 While various studies showed contrary responses of fracture toughness with increased fiber content, it may depend on the extent of fiber adhesion with matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The fracture toughness of FRP composites is governed by the properties of the individual component and the interaction between fiber and matrix. Energy spent in debonding, fiber breakage, Fibrillation of fiber, and crack growth in the matrix due to stress concentration at the crack tip contributes to fracture toughness 23,24 . Previous studies show a higher decrease in fracture toughness of composites with reinforcement of alkali‐treated natural fibers compared to untreated, caused by restriction to debonding and pull out of fibers that do not allow energy dissipation 25 .…”
Section: Introductionmentioning
confidence: 99%